Integrated approach of the dynamic characteristics optimization for spacecraft’s technical systems on the exploratory tests; MATEC Web of Conferences; Vol. 48 : Space Engineering - Dmitriev V. S. Viktor Stepanovich (Spacecrafts and Devices, 2016)
Title screen